2023
DOI: 10.2106/jbjs.oa.22.00138
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Academic Attributes of Matched and Unmatched Orthopaedic Surgery Residency Applicants are Narrowing

Abstract: Background:Orthopaedic surgery remains one of the most competitive residency specialties, with the number of applicants outpacing the availability of residency positions each year. The purpose of this study was to analyze present-day orthopaedic surgery match data, identify differences between matched and unmatched applicants, and compare our findings to previous trends.Methods:Applicant data from the National Resident Matching Program from 2016 to 2022 were analyzed. The number of matched and unmatched US all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…10,11 In comparing our study with these results, we assume applicants attend each interview offer they receive and rank each program they interview at, however, given the competitive nature of the orthopaedic surgery match this assumption is likely to hold true in a great majority of cases. Furthermore, Sudah et al 12 found matched students had 7.7 volunteer experiences compared with 7.0 in unmatched; nearly, the same as the 7.61 and 7.05 volunteer experiences we found in matched and unmatched applicants. These similarities provide confidence that our results are valid and can be generalized to the entire orthopaedics' applicant pool.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…10,11 In comparing our study with these results, we assume applicants attend each interview offer they receive and rank each program they interview at, however, given the competitive nature of the orthopaedic surgery match this assumption is likely to hold true in a great majority of cases. Furthermore, Sudah et al 12 found matched students had 7.7 volunteer experiences compared with 7.0 in unmatched; nearly, the same as the 7.61 and 7.05 volunteer experiences we found in matched and unmatched applicants. These similarities provide confidence that our results are valid and can be generalized to the entire orthopaedics' applicant pool.…”
Section: Discussionsupporting
confidence: 85%
“…Rynecki et al 10 found matched applicants to have a mean USMLE step 1 score of 248 and USMLE step 2 score of 255 compared with a mean USMLE step 1 score of 240 and USMLE step 2 score of 246 in unmatched applicants. In addition, Sudah et al 12 found mean USMLE step 1 and 2 scores to be 248 and 255, respectively, in matched applicants and 240 and 247 in unmatched applicants. These results are similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations